Case report: Melanosis coli combined with colon cancer, causality or coincidence? - Zhao, Wei; Chen, Jianan; Xing, Hongbin; Yu, Jun; Liu, Qian (Frontiers in Surgery, 2022)
The habitual use of laxative containing anthraquinone glycosides is considered to be the main cause of melanosis coli (MC). In the past, most scholars considered MC to be a benign and reversible disease. However, new evidence has emerged that MC may increase the risk of colon cancer. Here, we report a typical case of a 48-year-old woman diagnosed with MC and colon cancer. Through a literature review of previous basic and clinical studies, we summarize existing evidence that reveals the possible association between MC and colon cancer. Although this case cannot establish causality between MC and colon cancer, a high level of clinical vigilance for occurrence of colon cancer in patients with MC should be maintained.